PENYUSUNAN STANDAR KUALITAS PRODUK PADA KOPERASI USAHA RUMAH BATIK SETU DI TANGERANG SELATAN - Rodhiah; Aisyah, Anggun; Nuraisyah, Iis (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Standard Operating Procedures are the backbone of a successful business, allowing us to work whenever we choose. Standard operating procedures (SOPs) are a vital component of quality management practice. The effectiveness of SOP is highly dependent on the owner and all employees' commitment to enhancing the quality of the manufactured goods. At the Setu batik house business cooperative in South Tangerang, Student Creativity Program (PKM) is conducted. Setu batik house, often known as RBS, is a collection of company cooperatives that manufacture a variety of written batik products and stamps. In addition, it produces hijabs made of Parisian fabric with contemporary batik patterns. The PKM activity method entails support coming immediately to the RBS location and doing FGD with the board and multiple members. The outcomes of the activity revealed that RBS SOPs were organized in pocketbooks and laminated posters were affixed on the walls of the operating room. The resulting SOP can serve as a guide for partners, both administrators and members, in the production of batik products that conform to defined criteria.